2020
DOI: 10.33602/mebm.3.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenomics of murine melanoma cell lines C57/B1 and B16-F0

Abstract: In melanoma, one of the most aggressive human tumors, early diagnosis is still the best strategy to increase survival rates. C57/B1 and B16-F0 are murine cell lines frequently applied in basic and applied melanoma research. Thus, it is striking, that cytogenomic features of these two cell lines are not known yet. In the present study, molecular cytogenetics and array-comparative genomic hybridization were done in C57/B1 and B16-F0 cells and the resulting imbalances and breakpoints were translated into the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…As a numerically variant karyotype with ~95 chromosomes was already reported in 1982 3 , it can be concluded that the MTLC-1 cell line remained relatively stable during the last 40 years, as also reported for other murine cell lines before. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] Like most of these cell lines, MTLC-1 also showed several dicentric chromosomes normally considered to be instable; also, MTLC-1 is one of the few cell lines with a stable neocentric chromosome. 19,22 By the molecular cytogenetic characterization scheme applied here, a detailed characterization of numerical and structural changes of MTLC-1 was performed, which enabled the determination of ploidy-grade, individual chromosome numbers and involved rearrangements.…”
Section: Discussionmentioning
confidence: 96%
“…As a numerically variant karyotype with ~95 chromosomes was already reported in 1982 3 , it can be concluded that the MTLC-1 cell line remained relatively stable during the last 40 years, as also reported for other murine cell lines before. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] Like most of these cell lines, MTLC-1 also showed several dicentric chromosomes normally considered to be instable; also, MTLC-1 is one of the few cell lines with a stable neocentric chromosome. 19,22 By the molecular cytogenetic characterization scheme applied here, a detailed characterization of numerical and structural changes of MTLC-1 was performed, which enabled the determination of ploidy-grade, individual chromosome numbers and involved rearrangements.…”
Section: Discussionmentioning
confidence: 96%
“…The first cytogenomic characterization of the tumor cell line I-10 revealed a slightly hyperdiploid karyotype of 43 chromosomes, with relatively few imbalances and breakpoints for a cell line that is in cell culture for around 55 years. Interestingly, I-10 is a tumor cell line with dicentric chromosomes, which are normally considered to be unstable [5,[13][14][15][16][17][18][19][20][21][22][23][24][25]. It is one of the few cell lines with a stable neocentric chromosome [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, I-10 is a tumor cell line with dicentric chromosomes, which are normally considered to be unstable [5,[13][14][15][16][17][18][19][20][21][22][23][24][25]. It is one of the few cell lines with a stable neocentric chromosome [20,21]. Murine multicolor banding (mcb), along with CMA, enabled a detailed characterization of numerical and structural changes in the I-10 cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation